2014
DOI: 10.1080/10543406.2014.1000545
|View full text |Cite
|
Sign up to set email alerts
|

Sample size calculation based on efficient unconditional tests for clinical trials with historical controls

Abstract: In historical clinical trials, the sample size and the number of success in the control group are often considered as given. The traditional method for sample size calculation is based on an asymptotic approach developed by Makuch and Simon (1980). Exact unconditional approaches may be considered as alternative to control for the type I error rate where the asymptotic approach may fail to do so. We provide the sample size calculation using an efficient exact unconditional testing procedure based on estimation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 22 publications
2
4
0
Order By: Relevance
“…Studies have indicated that miR-126-3p is poorly expressed in various tumors, including hepatocellular carcinoma, a finding which was consistent with the results of our study 19 . The downregulation of miR-126-3p has also been flagged in cervical cancer tissues when compared with normal cervical tissues,28, 29, 30 whereas its level in cervical mucus was found to be increased among patients with cervical cancer 31 . Furthermore, decreased miR-126 expression has been previously linked with pancreatic cancer 24, 32.…”
Section: Discussionsupporting
confidence: 92%
“…Studies have indicated that miR-126-3p is poorly expressed in various tumors, including hepatocellular carcinoma, a finding which was consistent with the results of our study 19 . The downregulation of miR-126-3p has also been flagged in cervical cancer tissues when compared with normal cervical tissues,28, 29, 30 whereas its level in cervical mucus was found to be increased among patients with cervical cancer 31 . Furthermore, decreased miR-126 expression has been previously linked with pancreatic cancer 24, 32.…”
Section: Discussionsupporting
confidence: 92%
“…The power of the study will be maximized over all possible critical values for each first stage response by using the branch-and-bound intelligent algorithm. The monotonic ordering the second stage critical value is intuitive and consistent with existing approaches [3, 13, 5, 20, 21, 22, 5, 23, 24]. The power gain of the proposed approach as compared to the KC approach is generally substantial.…”
Section: Discussionsupporting
confidence: 76%
“…As compared to the exact approach for sample size calculation, (Lloyd, 2007, 2014, 2008a; Shan, 2013; Shan, Ma, Hutson, & Wilding, 2012; Shan & Ma, 2016; Shan, 2015; Shan, Wilding, Hutson, & Gerstenberger, 2016; Shan, Moonie, & Shen, 2016; Shan, 2015), the existing GEE approach does not guarantee type I and II error rates although it is computationally easy with a closed form. With the wide availability of powerful computers or supercomputers, exact sample size computation is practical and feasible.…”
Section: Discussionmentioning
confidence: 99%